2017
DOI: 10.1002/pssb.201700038
|View full text |Cite
|
Sign up to set email alerts
|

Tunable structural and electrical properties of zigzag CdS nanotubes: A density functional study

Abstract: We report structural and electrical properties such as wall thickness, binding energy, curvature energy, band‐gap energy, work function etc. of various zigzag CdS nanotubes within the framework of density functional theory. Binding energy calculation reveals that all the nanotubes studied here are stable and they follow classical elasticity law. The wall thickness, band‐gap, and work function of the tubes are found to decrease with increasing tube diameter. Quantitatively, the band‐gap may be tuned from 1.711 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…To date, significant efforts were made to develop 1D nanostructured materials (such as nanotubes, nanorods, and nanowires) in photocatalysis because of their unique geometrical and electronic properties. [ 25–28 ] Previously, we reported that photogenerated electrons and holes could be spatially separated along 1D CdSe nanorods, which significantly enhanced the photocatalytic hydrogen production activities with spatially separated dual cocatalysts. [ 29 ] Similar phenomena was observed in various semiconductors, which demonstrated the advantages of rationally assembling cocatalysts using spatial charge separation properties.…”
Section: Introductionmentioning
confidence: 99%
“…To date, significant efforts were made to develop 1D nanostructured materials (such as nanotubes, nanorods, and nanowires) in photocatalysis because of their unique geometrical and electronic properties. [ 25–28 ] Previously, we reported that photogenerated electrons and holes could be spatially separated along 1D CdSe nanorods, which significantly enhanced the photocatalytic hydrogen production activities with spatially separated dual cocatalysts. [ 29 ] Similar phenomena was observed in various semiconductors, which demonstrated the advantages of rationally assembling cocatalysts using spatial charge separation properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, electron‐hole recombination process is suppressed . Therefore, significant efforts have been made to design 1D CdS based materials (such as nanotubes, nanorods and nanowires) for photo‐catalytic applications . For example, Bandura et al.…”
Section: Introductionmentioning
confidence: 99%